The reality of kurdistan under the iranian-ottoman treaties (1514-1847) - Saeed, Dindar Issa (Humanities Journal of University of Zakho, 2023)
The Battle of Chaldiran, which broke out between the Safavid and Ottoman states in the year 1514 AD, marked the opening A long historical period of conflict between them, which extended for more than three centuries, during which the country of Kurdistan was its focus, as it constituted a natural barrier separating the two powers.The conflict developed further due to the ambitions of the new Safavid state, which aimed to extend its influence outside its regional borders at the expense of Kurdistan.This conflict prompted the two countries to resolve their differences through negotiations and dialogue, after depleting their capacities for centuries, with the change in the balance of power in favor of other countries, especially Britain and Russia.Treaty of Amasya 1555 AD - Treaty of Farhad Pasha (Constantinople) 1590 AD - Treaty of Nasuh Pasha 1612 AD - Treaty of Sarau 1618 AD - Treaty of Zahab (Palace of Shirin) 1639 AD - First Treaty of Erzurum 1823 AD and the Second Treaty of Erzurum 1847 AD, which affected one way or another with another on Kurdistan geographically, politically, economically and socially, and this after it was fragmented between them into areas of influence. We will try to study this subject, which has a historical-political formula, according to a major problem Regarding the position of Kurdistan in the Iranian-Ottoman treaties, and its impact on its geographical, political, economic and social structure, based on this problem, we will rely in our study on the historical approach with its descriptive and analytical tools, focusing on analyzing the content of the treaties. We will address the research topic according to the following elements: 1- The Iranian-Ottoman conflict after 1514 AD and its renewal during the reign of Tahmasp I (1524 AD - 1576 AD). 2- The Iranian-Ottoman treaties (1555 AD - 1847 AD). 3- The impact of treaties on the geographical, political, economic and social structure of Kurdistan.